1998
DOI: 10.1084/jem.188.2.327
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Ischemia Enhances Polyamine Oxidation: Identification of Enzymatically Formed 3-Aminopropanal as an Endogenous Mediator of Neuronal and Glial Cell Death

Abstract: To elucidate endogenous mechanisms underlying cerebral damage during ischemia, brain polyamine oxidase activity was measured in rats subjected to permanent occlusion of the middle cerebral artery. Brain polyamine oxidase activity was increased significantly within 2 h after the onset of ischemia in brain homogenates (15.8 ± 0.9 nmol/h/mg protein) as compared with homogenates prepared from the normally perfused contralateral side (7.4 ± 0.5 nmol/h/mg protein) (P <0.05). The major catabolic products of polyamine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
109
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(110 citation statements)
references
References 75 publications
(103 reference statements)
1
109
0
Order By: Relevance
“…Recent evidence demonstrated that under certain conditions PAO could directly act on spermine and spermidine to produce putrescine (Ivanova et al, 1998). Our data indicate that the putrescine is largely formed by PAO action on N 1 -acetylspermidine and that the contribution of PAO direct oxidation of spermidine to putrescine appears to be minimal.…”
Section: Fig 2 Amentioning
confidence: 49%
See 2 more Smart Citations
“…Recent evidence demonstrated that under certain conditions PAO could directly act on spermine and spermidine to produce putrescine (Ivanova et al, 1998). Our data indicate that the putrescine is largely formed by PAO action on N 1 -acetylspermidine and that the contribution of PAO direct oxidation of spermidine to putrescine appears to be minimal.…”
Section: Fig 2 Amentioning
confidence: 49%
“…1) and previous studies (Dogan et al, 1999a,b), inhibition of PAO with MDL 72527 significantly attenuated putrescine levels at 1 day after CNS injury. This suggests that the induction of SSAT (Zoli et al, 1996) and PAO (Baudry and Najm, 1994;Hayashi and Baudry, 1995;Ivanova et al, 1998), which convert spermine and spermidine to putrescine, probably is a major pathway accounting for putrescine accumulation at 1 day. These studies did not attempt to correlate SSAT enzymatic activity to N 1 -acetylspermidine levels because the SSAT assay may overestimate N 1 -SSAT activity (Persson and Pegg, 1984;Gerner et al, 1993).…”
Section: Attenuated Putrescine Accumulationmentioning
confidence: 99%
See 1 more Smart Citation
“…On one hand, spermine might be protective by attenuating excessive inflammatory response when given at a moderate dose (for example, 10 kg/mL). On the other hand, it might be converted enzymatically by polyamine oxidases into cytotoxic metabolites (for example, 3-aminopropanal), and mediate cytotoxicity through direct chemical modification of cell membrane proteins (35,36). Although the observed dual (both beneficial and injurious) effects of spermine may pose limitations to its clinical use as a potential therapeutic agent, it provides us with a unique tool to elucidate the complex mechanisms underlying the pathogenesis of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Other neuroprotective mechanisms of AG may be related to its free radical scavenging properties (35,39). Also, a number of cellular metabolic pathways about AG neuroprotective functions relate to methylglyoxal (MG) inhibition (40). MG acts as either an endogenous fatal substance (41) or an effective source of ROS (42), which frequently build up in the hippocampal neurons in hyperglycemia (43,44,45).…”
Section: Discussionmentioning
confidence: 99%